EFEKTIVITAS PROGRAM PENYULUHAN ZERO WASTE UNTUK MENINGKATKAN KESEHATAN MASYARAKAT DI LINGKUNGAN KELUARGA URBAN DALAM KONTEKS KANG PISMAN - Mira Rahayu; Lenny Nuraeni (IKIP Siliwangi, 2026)
This study aims to analyze the effectiveness of the zero waste counseling program in improving public health within urban families, specifically in the context of the Kang Pisman program (Reduce, Separate, and Utilize). The research was motivated by the increasing household waste problem in urban areas, which directly impacts community health. A mixed methods approach was employed using an explanatory sequential design. Quantitative data were first collected from 40 respondents through questionnaires, followed by qualitative data through interviews and observations to strengthen the findings. The results indicate that the zero waste counseling program significantly improves public health, as shown by a correlation value of 0.7494 with a contribution of 59.6%. The program encouraged changes in knowledge, attitudes, and behaviors related to waste management, such as waste separation, reducing single-use plastics, and reusing both organic and inorganic materials. However, several challenges remain, including limited supporting facilities, low participation among some residents, and persistent old habits. Overall, the study concludes that zero waste counseling is effective in fostering awareness and healthy living practices in urban families and has great potential as a sustainable strategy to enhance community health quality.